Formulation and Evaluation of Patchouli Oil Bath Bomb with Citric Acid as an Acidic Component - Rochman, M Fatchur; Nurkhayati, Nurkhayati; Shabrina, Ayu (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2025)
Conventional bath bombs contain only acidic and basic agents for effervescence, without any antibacterial or pharmacologically active ingredients. This study developed a bath bomb formulation enriched with bioactive compounds to provide antibacterial and therapeutic benefits beyond conventional cosmetic use. Patchouli alcohol is contained in the essential oil present in patchouli leaves, which is known to have antibacterial activity. Bath bomb is a spa product that can provide a relaxing atmosphere during bathing, which is used by soaking. Bath bombs were made using the mixing method with citric acid variations FI 26.3%, F2 33.3% and F3 38.5%. Evaluation of characteristics included organoleptic properties, weight uniformity, pH, hardness, dissolution effectiveness, foam height and stability test, water content, and geometric surface area test. The results of the characteristics bath bombs showed that three formulas gave good evaluations. The formulas did not significantly affect the pH of the bath bomb formulations. However, higher citric acid levels influenced organoleptic properties, weight uniformity, hardness, dissolution time, moisture content, geometric surface area, and foam height stability.